2022
DOI: 10.3389/fpsyg.2022.915572
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the value of organizational support, engagement, and psychological wellbeing in the volunteer context

Abstract: In Australia, young adults are more likely to experience psychological distress than other age-groups. Accordingly, volunteer work engagement may act as an important tool for supporting psychological wellbeing. The present study relies on the job demands–resources model and self-determination theory to help understand the negative consequences of high work demands and the importance of effective organizational support to enhance positive mental health outcomes. To address research gaps, the current study explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Their findings suggested that organisations may need to provide greater resources to support volunteer work engagement and wellbeing in younger adults. 37 These findings may be useful for not‐for‐profit organisations on advising how to develop better recruitment and volunteer retention strategies for younger or unrepresented adults.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Their findings suggested that organisations may need to provide greater resources to support volunteer work engagement and wellbeing in younger adults. 37 These findings may be useful for not‐for‐profit organisations on advising how to develop better recruitment and volunteer retention strategies for younger or unrepresented adults.…”
Section: Discussionmentioning
confidence: 94%
“…Dekel et al 37 suggested that future research needs to include a range of measures that capture the motivational and behavioural factors in younger people, such as self‐reported measures of volunteer engagement, psychological wellbeing and perceived organisational support. Their findings suggested that organisations may need to provide greater resources to support volunteer work engagement and wellbeing in younger adults 37 . These findings may be useful for not‐for‐profit organisations on advising how to develop better recruitment and volunteer retention strategies for younger or unrepresented adults.…”
Section: Discussionmentioning
confidence: 99%
“…The JD-R model [9] is widely used by researchers (e.g., [11][12][13][14][15][16][17][18][19]) and has helped eliminate some of the limitations of previous theoretical models (e.g., Karasek's job-demand-control model [20]) [21]. The authors of a meta-analytic review based on longitudinal studies concluded that the JD-R model provides a valuable theoretical framework regarding employees' wellbeing [22].…”
Section: Introductionmentioning
confidence: 99%